The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1071/sr16344
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of CO2 and O2 as index for categorising soil biological activity in sugarcane areas under contrasting straw management regimes

Abstract: This study was developed in a sugarcane area under contrasting management regimes defined by mechanical green harvesting (GH) and burning harvesting (BH) to test the hypotheses that the ratio of carbon dioxide (CO2) and oxygen (O2), known as the apparent respiratory quotient (ARQ), can be used to categorise soil biological activity. The study aimed to (i) examine the profile and relationship between the CO2 flux (FCO2) and the O2 flux (FO2) in a sugarcane area under mechanical harvesting with straw burning (BH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…A synergy exists between both respirations, and they compete for the availability of nutrients and O 2 (Ben-Noah and Friedman 2018). Doran and Parkin (1984) and Almeida et al (2018) also reported RQ > 1 values after rainfall events and increased soil water content. However, the RQ > 1 values observed in this study were not associated with rainfall events Table 7.…”
Section: Ratio Of Soil Co 2 Emission and O 2 Absorption (Rq)mentioning
confidence: 91%
See 4 more Smart Citations
“…A synergy exists between both respirations, and they compete for the availability of nutrients and O 2 (Ben-Noah and Friedman 2018). Doran and Parkin (1984) and Almeida et al (2018) also reported RQ > 1 values after rainfall events and increased soil water content. However, the RQ > 1 values observed in this study were not associated with rainfall events Table 7.…”
Section: Ratio Of Soil Co 2 Emission and O 2 Absorption (Rq)mentioning
confidence: 91%
“…The soil FO 2 rate (dO 2 /dt) was calculated via linear interpolation of the concentration values as a function of time, taking into account the atmospheric pressure, temperature, and volume of the gas trapped in the chamber by using FO 2 (Smagin et al 2016;Almeida et al 2018) as follows:…”
Section: Characterisation Of the Areasmentioning
confidence: 99%
See 3 more Smart Citations